Programming the Public Sphere - Elayne M. Harris (Adult Education Research Conference, 2004)
Adult educators are not alone in their interest in a critical education for citizenship. Still, there is no tradition of applied, middle-range work with respect to programmes. This study is a modest beginning on the slippery, delicate, paradox-ridden muddle of operationalizing a critical education for citizenship in Canada.